(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2014)
Recensiamo Marie-Laure Ryan e Jan-Noël Thon eds, Storyworlds across Media. Toward a Media-Conscious Narratology